1997
DOI: 10.2337/diab.46.2.s119
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Coronary Flow Reserve in NIDDM: A Possible Role for Diabetic Cardiopathy in Humans

Abstract: Diabetic cardiopathy represents a cardiac disorder with involvement of myocardial, interstitial, coronary, and neural structures. One of the main manifestations refers to coronary microangiopathy, which has not yet been clearly identified. Coronary hemodynamics, including the determination of coronary flow reserve, were therefore analyzed in normal subjects and in nine patients with NIDDM and clinically suspected coronary heart disease but normal coronary arteriogram. Coronary flow reserve was determined as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 0 publications
5
50
0
2
Order By: Relevance
“…This limitation is particularly disadvantageous, as the diabetic heart works on a higher level of oxygen demand than the heart of CAD patients, at least as reflected by the rate-pressure product. Our observation that myocardial blood flow during stress and coronary flow reserve are also reduced is in line with the above findings, confirming observations by PET and angiography [10][11][12]. A noteworthy observation, and one not shown before, was that global perfusion in patients with macrovascular CAD was impaired to the same extent as in diabetic patients with microvascular disease (Fig.…”
Section: Myocardial Perfusion In Type 2 Diabetic Patientssupporting
confidence: 80%
See 1 more Smart Citation
“…This limitation is particularly disadvantageous, as the diabetic heart works on a higher level of oxygen demand than the heart of CAD patients, at least as reflected by the rate-pressure product. Our observation that myocardial blood flow during stress and coronary flow reserve are also reduced is in line with the above findings, confirming observations by PET and angiography [10][11][12]. A noteworthy observation, and one not shown before, was that global perfusion in patients with macrovascular CAD was impaired to the same extent as in diabetic patients with microvascular disease (Fig.…”
Section: Myocardial Perfusion In Type 2 Diabetic Patientssupporting
confidence: 80%
“…Both abnormalities have also been observed in patients with type 1 and type 2 diabetes using techniques like traditional echocardiography [8,9], angiography and positron emission tomography [10][11][12]. However, there is a lack of evidence-based treatment strategies for these abnormalities in the diabetic heart, probably because the techniques mentioned above are not well suited for sequential studies after pharmacological intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The baseline CFVR values in this study were concordant with the results of previous studies using positron emission tomography 2,6,7,14,15 and Doppler guidewire. 3,4,16 Coronary microvascular abnormalities and endothelial dysfunction have been reported in diabetic patients even with normal left ventricular systolic function and angiographically normal coronary arteries, 4 and several mechanisms have been suggested to explain the impaired coronary vasodilatory function in diabetic patients, 6 including hyperglycemia, hyperinsulinemia, 7 advanced glycosylation end-products and lipoprotein modification.…”
Section: Baseline Studysupporting
confidence: 82%
“…Changes in myocardial microvasculature in diabetic patients have been demonstrated by histopathological studies 19 and by invasive studies which have shown maximal coronary blood flow reserve and impaired endothelialdependent epicardial coronary vasodilatation. 2,20,21 Furthermore, non-invasive functional studies involving PET have shown significant impairment of MBF during dipyridamole stress in patients with diabetes. 4 In this study, we used a method to determine MCEderived MBF in absolute units of blood volume per time in relation to myocardial mass (ml/min/g) which has been recently developed by Vogel and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…These include morphological 1 and functional abnormalities on non-invasive or invasive imaging. [2][3][4][5] Myocardial contrast echocardiography (MCE) utilises compressible membrane-stabilised microbubbles containing gas, which behaves similarly to red blood cells, rendering them an excellent tracer for blood flow measurements. Destruction of microbubbles and observation of the gradual refill into the myocardium is the foundation for the evaluation of myocardial perfusion using real-time MCE.…”
Section: Introductionmentioning
confidence: 99%